Herbicidas Postemergentes para Uso en Ornamentales - E. Vanessa Camoverde; Chris Marble; Jeffrey G. Norcini (EDIS)
This is the Spanish-language version of ENH95/WG059: Postemergent Herbicides for Use in Ornamentals. Postemergent herbicides are applied directly to weeds. This 5-page fact sheet is largely comprised of two tables: table 1 lists postemergent herbicides that can be safely used over the top of some ornamentals when used according to label directions; table 2 lists postemergent herbicides that are registered for use around ornamental plants when applied as a directed spray. Written by E. Vanesssa Campoverde, Chris Marble, and Jeffrey G. Norcini, and published by the Environmental Horticulture Department, October 2016.